Effect of information system awareness on organizational success of tourism firms in Turkey - Terzioğlu, Ozan (My University, 2001)
Turizm sektörünün, özellikle ihtiyaç duyduğu yatırımla karşılaştırılınca, bir ülkeye önemli miktarda ihracat sağlama potansiyeli vardır. Bu potensiyelden tam olarak yararlanabilmek için, bir ülke mümkün olduğu kadar fazla miktarda varlıklı turist çekmelidir. Bu turistler; turistik eşya, daha fazla tarihi mekanda giriş ücreti, daha pahalı otel ve restoranlar ve diğer ilgili servislere hatırı sayılır miktarda para harcarlar. Yukarıdaki hedefi gerçekleştirebilmek için, bir ülke turist çeken mekanlarının özellikleri kadar, organizasyonlarının verdiği servisle de ünlü olmalıdır. Her ne kadar diğer turizm servislerine de uygulanabilir kısımları olsa da, bu çalışmanın ana amacı, tarih, kültür ve dine özel ilgisi olan varlıklı yabancı turiste hitab eden Anadolu Turu'nun kritik başarı faktörlerini(hep birlikte servis kalitesini belirlerler) ortaya çıkarmaktır. Bu çalışma tarafından ortaya çıkarılan kritik başarı faktörlerinin, her kritik başarı faktörünün hedef kitlenin istediği şekilde yerine getirilmesini sağlayacak kuralları ve yönetmelikleri belirleyecek ve güncelleyecek bilgileri toplayacak ve analiz edecek enformasyon sistemlerinin odak noktasını belirleme potansiyeli olabilir.

Tourism sector has the potential of generating significant amounts of exports for a country, especially compared to the amount of investment required. In order to fully realize this potential, a country must attract as much wealthy tourists as possible, who usually spend significant amount of money on extras like souvenirs, entrance fees at more historical places, more expensive hotels and restaurants, and other services. To this end, a country must become famous by the tourism service its organizations provide, in addition to the attributes of its tourist attractions. Although parts of it can be applied to most other types of tourism services, this study primarily aims to identify the critical success factors(collectively determine the actual service quality) of the Anatolian Tour, which caters to wealthy individuals with special interest in history, culture and religion. The critical success factors identified by this study may have the potential to form the focus of the information systems that would collect and analyze data that would determine and update the standards and regulations to make sure each critical success factor is fulfilled, in the capacity as required by the intended audience.
Keywords: Turizm Işletmeleri